Efeitos do esteróide anabolizante associado ao exercício físico resistido em parametros bioquímicos, inflamatórios e neuroquímicos em ratas - Pereira, Aline da Silva (2023)
Regular physical exercise is the best strategy for maintaining a healthy body and autonomous aging. However, in recent years the search for the perfect body has contributed to the search for anabolic resources that accelerate this process. Thus, this study aimed to evaluate the effects of the anabolic androgenic steroids (AASs) testosterone and oxandrolone in vitro and in vitro through three experimental protocols. In experimental protocol I, a concentration curve using the steroids testosterone and oxandrolone in polymorphonuclear cells (PBMCs) was evaluated in vitro. In experimental protocol II and III, in vivo, adult rats were treated with the steroid oxandrolone or testosterone for 30 days and subjected to resistance exercise. In these protocols, oxidative, inflammatory, neurochemical parameters and purinergic signaling were analyzed. In these different protocols it was possible to establish that the anabolic steroid oxandrolone and testosterone modulate the activity of ectonucleotidases and increase oxidative stress in PBMCs. In the in vivo experimental protocol, it was possible to verify that the administration of oxandrolone modulates the activity of peripheral and central ectoenzymes, and the MAP kinase (MAPK) pathway in the central nervous system, while exercise minimizes the effects of the adjacent use of oxandrolone in the cortex. The compound with different testosterones has shown to have a potent neuroinflammatory effect and surprisingly, resistance exercise reverses this data at the level of control in almost all of these parameters. We conclude that the steroids evaluated here have different responses in modulating the purinergic system in different cells. We can also highlight that resistance exercise on stairs for a period of 30 days protects the body from possible damage caused by the use of steroids in the doses and time studied here.